2016
DOI: 10.1080/23273798.2016.1200732
|View full text |Cite
|
Sign up to set email alerts
|

Modelling verb selection within argument structure constructions

Abstract: This article looks into the nature of cognitive associations between verbs and argument structure constructions (ASCs). Existing research has shown that distributional and semantic factors affect speakers' choice of verbs in ASCs. A formal account of this theory has been proposed by Ellis, N. C., O'Donnell, M. B., & Römer, U. [(2014a). The processing of verb-argument constructions is sensitive to form, function, frequency, contingency and prototypicality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…Our findings confirmed the previous literature (Ellis and Ferreira-Junior, 2009;Matusevych et al, 2016) that input frequency determines its production frequency in the L2. Cue availability made an equally high contribution to L2 production frequency at the two levels of L2 competence.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings confirmed the previous literature (Ellis and Ferreira-Junior, 2009;Matusevych et al, 2016) that input frequency determines its production frequency in the L2. Cue availability made an equally high contribution to L2 production frequency at the two levels of L2 competence.…”
Section: Discussionsupporting
confidence: 93%
“…To address this gap in the literature, in this article we use a computational model of learning argument structure constructions from bilingual input. We choose this model, because it has been used for simulating bilingual learning of argument structure constructions (Matusevych, Alishahi, & Backus, 2016b, 2017, and it allows for measuring the amount of CLI in this domain. Our goal in the present study is to demonstrate how the amount of CLI can be measured in the learning and use of such constructions, and how a CLI measure can be employed to explain the patterns of language use observed in the model.…”
Section: Quantifying Cross-linguistic Influencementioning
confidence: 99%
“…The idea comes from the study of Anderson (1991), who implemented the model of human category learning. Stevenson (2008, 2010) were the first to simulate the learning of argument structure constructions using the same algorithm, while Matusevych et al (2016bMatusevych et al ( , 2017 adapted the model for bilingual learning. In all the mentioned studies, the model was demonstrated to replicate certain types of human behavior in the respective domain.…”
Section: Model Overviewmentioning
confidence: 99%
See 1 more Smart Citation